The association among teacher-student relationship, subjective well-being, and academic achievement: Evidence from Chinese fourth graders and eighth graders - Zhou, Da; Liu, Shuting; Zhou, Hao; Liu, Jian; Ma, Yue (Frontiers in Psychology, 2023)
Abstract: This study compared the teacher-student relationship, subjective well-being, and academic achievement between fourth graders and eighth graders, and examined whether and how subjective well-being played a mediating role concerning teacher-student relationship and academic achievement across the two grades. The participants included 19,845 fourth graders and 11,691 eighth graders from a city in central China. The findings indicated that (1) compared with eighth graders, fourth graders reported significantly higher mean scores in the teacher-student relationship, subjective well-being, and academic achievements; (2) a positive teacher-student relationship can promote students’ academic achievement both directly and indirectly through subjective well-being across the two groups; (3) The mediating effect of subjective well-being accounted for 42.8% of the total effects between teacher-student relationship and academic achievement for fourth graders, which was higher than that for eighth graders (22.7%). Limitations and future directions are elaborated.